In Vivo Evaluation of a Novel Control Algorithm for Left Ventricular Assist Devices Based Upon Ventricular Stroke Work. Issue 1 (13th April 2022) - Habigt, Moriz A.; Hein, Marc; Gesenhues, Jonas; Abel, Dirk; Rossaint, Rolf; Mechelinck, Mare
Abstract : The physical fitness of patients with terminal heart failure and an implanted left ventricular assist device (LVAD) might be improved by load-adaptive control of the LVAD. In this study, three control strategies for LVAD were compared in eight pigs: (1) a constant stroke work (CSW) control strategy that ensures a constant ventricular load using ventricular stroke work as the control variable; (2) a work ratio (WR) controller that maintains a constant ratio of ventricular work to hydraulic pump work; and (3) a controller that maintains the pump pace at a constant speed (CS). Biventricular heart insufficiency was induced by increased isoflurane application, and preload, afterload, and contractility alterations were performed. LVAD speed changes were significantly more pronounced in all load interventions with the CSW control strategy (preload: P < 0.001 vs. CS and P = 0.004 vs. WR; afterload: P < 0.001 vs. CS and P < 0.001 vs. WR; contractility: P < 0.001 vs. CS and P < 0.001 vs. WR). However, a significant difference in systemic flow only became evident in the experiments upon afterload increase ( P < 0.001 vs. CS and P = 0.004 vs. WR). An implementation of an evolved version of the CSW control strategy that dispenses with invasively measured parameters might be feasible for clinical use.